Service Quality and Trust as Predictors of Online Purchasing Decisions Mediated by Perceived Risk - Sutisna Sutisna; Mochamad Saefullah; Juwita Juwita (Journal of Consumer Sciences, 2023)
Online purchasing decision-making is currently faced with a lack of trust from consumers as a result of the inability of marketers to deliver services satisfactorily, which results in the emergence of risk perceptions in purchases. This study aimed to determine how the effect of seller service quality and consumer confidence on perceived risk and how they influence purchasing decisions. Another goal is to determine the role of perceived risk as an intervening variable. The design of this study was a cross-sectional survey of respondents in the city of Serang and its surroundings. The sampling technique used is purposive sampling. The survey used the Google form with a total of 129 respondents. The analysis method uses descriptive and inferential statistics and SMART PLS software is used for data processing. The results showed a significant negative effect of service quality on perceived risk and a significant negative effect of perceived risk on online purchasing decisions. Perceived risk is an intervening variable from consumer confidence to online purchasing decisions. Online purchasing can be enhanced by increasing trust and service and reducing perceived risk.